2019
DOI: 10.1186/s40249-019-0611-z
|View full text |Cite
|
Sign up to set email alerts
|

A community-based comprehensive intervention to reduce syphilis infection among low-fee female sex workers in China: a matched-pair, community-based randomized study

Abstract: BackgroundLow-fee female sex workers (FSWs) are at high risk of acquiring and spreading human immunodeficiency virus (HIV)/sexually transmitted diseases (STDs) in China. There is an urgent need to develop comprehensive intervention measures targeted towards low-fee FSWs to reduce HIV/STD infections. Thus, this study aimed to reduce HIV/STD infections among low-fee FSW through a matched-pair, community-based randomized intervention trial carried out in 12 cities in three provinces in China.MethodsFour cities fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…Furthermore, errors in antibiotic dosage have also been of concern. Other key factors, such as conjugal in delity, the absence of partners at prenatal appointments and reluctance in adhering to treatment protocols have also been reported by patients [27,31].…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, errors in antibiotic dosage have also been of concern. Other key factors, such as conjugal in delity, the absence of partners at prenatal appointments and reluctance in adhering to treatment protocols have also been reported by patients [27,31].…”
Section: Discussionmentioning
confidence: 85%
“…Of the 32 studies [16][17][18][19][20][21][22][23][24][25][26][29][30][31][32][33][34][36][37][38][39][40]42,[44][45][46][47][48][49][50][51]91] that reported on condom use, 21 were individual-RCT and 11 were cluster-RCT, though two studies reported results from the same cluster-RCT [17,20]. The interventions included in these studies varied (Table 4).…”
Section: Condom Usementioning
confidence: 99%
“…The interventions included in these studies varied (Table 4). Seventeen studies examined enhanced counselling or education sessions compared to standard HTS [16,18,25,26,29,30,33,35,36,[38][39][40]42,45,49,50,91], two studies examined the distribution of HIV self-testing kits relative to standard HTS [31,32], two studies from the same cluster-RCT examined community-based HTS [17,20] along with two other studies [22,34], one study included couple HTS relative to standard HTS [37], one study examined counsellor-delivered home-based HTS versus clinic-based HTS [21] and one study examined abbreviated HTS compared to standard HTS [48].…”
Section: Condom Usementioning
confidence: 99%
See 1 more Smart Citation
“…According to China national HIV/AIDs sentinel surveillance report from 2011 to 2015, low-tier FSWs exhibited higher than middle-and high-tier FSWs in HIV and syphilis prevalence, with a HIV prevalence of 0.1-0.2% in middle-and high-tier FSWs versus 0.4-0.6% in low-tier FSWs, and a syphilis prevalence of 1.6-1.9% in middle-and high-tier FSWs versus 3.6-4.6% in low-tier FSWs. A high prevalence of HIV and syphilis was found among Chinese low-tier FSWs [12,13]. Therefore, low-tier FSWs play an important role in facilitating HIV and STI transmission, and their high mobility could also introduce HIV/STI transmission from one place to another.…”
Section: Introductionmentioning
confidence: 99%